3D Printed Parts of Polylactic Acid Reinforced with Carbon Black and Alumina Nanofillers for Tribological Applications. Issue 1 (16th December 2020) - Cardoso, Paulo Henrique Machado; de Oliveira, Marcelo Ferreira Leão; de Oliveira, Marcia Gomes; da Silva Moreira Thiré, Rossana Mara
Abstract: 3D printing plays an important role in Industry 4.0 and has versatility to use different materials, including thermoplastic polymers. Polylactic acid (PLA), a bio‐based biodegradable polymer, is used as a potential replacement for petroleum‐based polymers in several applications, and is one of the most popular polymers used in 3D printing. Inorganic/organic nanoparticles can be incorporated in polymers to improve various properties such as thermal, mechanical, and tribological. This work investigates the effect of adding carbon black (CB) and alumina (ALM) nanofillers on the thermal, mechanical, and tribological properties of 3D printed PLA nanocomposites for tribological applications. Both nanofillers promoted progressive enhancement of thermal stability according to TGA. The improvement in the interaction between nanofillers and PLA matrix is revealed by an increase in viscosity of the nanocomposites. The nanocomposites containing 25%wt ALM and 75wt% CB presented better mechanical and wear properties, suggesting synergism between nanofillers and that CB may act as a compatibilizer between PLA and ALM. These results enable selecting the most suitable composition of nanofillers to be added to PLA to create filaments with better tribological properties.